HUBUNGAN SIKAP KERJA STATIS TERHADAP NYERI BAHU PADA PEKERJA MEMBATIK TULIS DI KAMPUNG BATIK LAWEYAN SURAKARTA - PURWASIH, DIAH RAHAYU (2010)
Purpose of this research to know the relation of position of batik statist activity writes to shoulder pain in bone at batik worker writes. Place of research in executing in Kampung Batik Laweyan Surakarta. This research method is survey or observation by using equate. Sample consisted of 30 batik worker writes. With sampling technique purposive sampling. Data analysis is applied to applies correlation of bivariate. Examination of analysis done by using Uji Normalitas with Uji Kolmogorov. All calculations is using program help SPSS Versi 115. From analysis obtained that there is the relation of position of static activity with shoulder pain in bone with result of coefficient correlation 0,492 and value signifikansi 0,006 < 0,05. Thereby earns in concluding that to the relation of position of static activity with its the rises shoulder pain in bone